2010
DOI: 10.1038/hr.2010.185
|View full text |Cite
|
Sign up to set email alerts
|

Aortic size index enlargement is associated with central hemodynamics in essential hypertension

Abstract: The aim of this study was to evaluate the association between brachial and central blood pressure (bBP and cBP) levels and aortic root dilatation (ARD) in essential hypertensive patients. A total of 190 untreated and treated essential hypertensive patients (mean age, 55±11 years) were considered for this analysis. We measured pulsatile hemodynamics and the proximal aortic diameter directly using tonometry, ultrasound imaging (echocardiography) and Doppler. Ninety-one hypertensive patients had an ARD (defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 33 publications
2
25
0
2
Order By: Relevance
“…In this study, carotid internal diameter was an independent prognostic factor for all-cause mortality, whereas circumferential wall stress, which integrates diameter, intimamedia thickness, and pressure, was not. Arterial enlargement is a process associated with supposedly normal aging 32 but has also been associated with pathological conditions, such as hypertension in menopausal women, 33 hypertension, 34,35 CKD, 6 and end-stage renal disease patients. 36 In hypertensive patients, an increase in aortic diameter has been independently associated with target organ damage, such as cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, carotid internal diameter was an independent prognostic factor for all-cause mortality, whereas circumferential wall stress, which integrates diameter, intimamedia thickness, and pressure, was not. Arterial enlargement is a process associated with supposedly normal aging 32 but has also been associated with pathological conditions, such as hypertension in menopausal women, 33 hypertension, 34,35 CKD, 6 and end-stage renal disease patients. 36 In hypertensive patients, an increase in aortic diameter has been independently associated with target organ damage, such as cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in accordance with numerous in vitro studies showing that cyclic stretch exerts a greater influence than static load on phenotype and growth of VSMCs (including synthesis of DNA, smooth muscle myosin, and collagen). [53][54][55] The diameter of the aortic root has been studied in hypertensives 52 : the higher the central PP, the larger the aortic root diameter, suggesting as discussed above a major role of pressure pulsatility on aortic root enlargement. MRI, which precisely investigates the geometry of aorta in hypertensives, showed that ascending aortic diameter and increased aortic arch length and width, as well as decreased aortic arch curvature, were highly correlated with increased central PP.…”
Section: Large Artery Alterations Large Artery Remodelingmentioning
confidence: 99%
“…The enlargement of proximal elastic large arteries with aging and elevated mean blood pressure has been extensively described in humans in studies using ultrasounds, particularly high-resolution echotracking systems. [43][44][45][46][47][50][51][52] The enlargement of large arteries, such as the thoracic aorta and the common carotid artery (CCA), is generally attributed to fracture of the load-bearing elastin fibers in response to the fatiguing effect of steady and pulsatile tensile stress. However, growth and apoptosis of VSMCs could also be involved.…”
Section: Large Artery Alterations Large Artery Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased left atrial and aortic root diameters can be observed in hypertension with high hs-CRP levels [22]. Milan et al [23] demonstrated a strict correlation between aortic size index and central hemodynamic parameters in patients with essential hypertension. Our results support this with a positive correlation with diastolic interventricular septum thickness, and aortic root and left atrium diameters.…”
Section: Discussionmentioning
confidence: 99%